Gogol on the man’s calling in European philosophy and Russian messianism - Malivskyi, A. M; Snitko, D. Y (Anthropological Measurements of Philosophical Research, 2022)
The purpose is to study that period of evolution of Gogol’s position, in which his ideas of russian messianism are most clearly outlined ("Selected Passages" and "The Author’s Confession"). To delineate the forms of determining the influence of messianism on his negative assessments of the anthropology of the Early New Age and the Enlightenment. Realization of the specified purpose presupposes, first, the analysis of his way of interpreting humanism in the European classical philosophy, and, secondly, to clarify the nature of his connection with the way of substantiating the idea of the Russian messianism. Theoretical basis. Our view of Gogol’s heritage is based on the conceptual positions of phenomenology, existentialism, and hermeneutics. Originality. It is revealed, that period of evolution of Gogol’s position, which most clearly outlines his ideas of russian messianism ("Selected Passages" and "The Author’s Confession"), his position on human nature and its calling is fundamentally different from the position of philosophy of Early New Age and the Enlightenment. If in the first case, it is a question of service to the russian empire, in the last one, it is a question of self-development of the person. Gogol’s dehumanization of those perceptions about the man that have occurred in European classical philosophy is a precondition in justification of russian messianism for him. One of its key factors is a narrow understanding of insight the ideas concerning the spiritual foundation of the world, namely – its reduction to the russian empire. Conclusions. Gogol’s philosophical doctrine of man is only partially described as belonging to the "philosophy of the heart". The disadvantage of this qualification is the impossibility of explaining the question of the origins in Gogol’s attempt to substantiate russian messianism. The article demonstrates that the deformation of the basic idea about the connectivity of man with the spiritual arche of the world is its substantive precondition for the philosophy of the Early New Age and the Enlightenment. Gogol narrows it down to the Russian Empire, which makes it impossible to positively delineate the orientations of the russian people. Therefore, his oeuvre during the work on "Selected Passages" and "The Author’s Confession" for future generations is a warning about the futility of a single russian path of development, isolated from European civilization. As the further development of russian thought and history proves, Gogol’s warning as a Ukrainian thinker really has not been heard. A vivid manifestation of this is the cave nationalism that we see today during the russian-Ukrainian war.